2018
DOI: 10.1002/syn.22061
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic cannabinoid CB2 receptors modulate [3H]‐Glutamate release at subthalamo‐nigral terminals of the rat

Abstract: Recent studies suggested the expression of CB2 receptors in neurons of the CNS, however, most of these studies have only explored one aspect of the receptors, i.e., expression of protein, messenger RNA, or functional response, and more complete studies appear to be needed to establish adequately their role in the neuronal function. Electron microscopy studies showed the presence of CB2r in asymmetric terminals of the substantia nigra pars reticulata (SNr), and its mRNA appeared is expressed in the subthalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 72 publications
(94 reference statements)
0
12
0
1
Order By: Relevance
“…The expression of faint CB 2 receptor immunolabeling in neurons and its absence in SGCs of canine DRG, partially agrees with previous findings in laboratory rodents, where only very weak immunoflorescence was found in basal conditions (56). Although CB 2 receptor was considered lacking in neurons and glial cells, recent literature highlights its expression in these cell types (57, 58), even in humans (54) and dogs (11, 59). Similarly to CB 1 (28), CB 2 receptor is upregulated in a variety of PNS and CNS diseases and is suggested as a promising pharmacological target in the management of chronic pain and neuroinflammation (2931, 56).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of faint CB 2 receptor immunolabeling in neurons and its absence in SGCs of canine DRG, partially agrees with previous findings in laboratory rodents, where only very weak immunoflorescence was found in basal conditions (56). Although CB 2 receptor was considered lacking in neurons and glial cells, recent literature highlights its expression in these cell types (57, 58), even in humans (54) and dogs (11, 59). Similarly to CB 1 (28), CB 2 receptor is upregulated in a variety of PNS and CNS diseases and is suggested as a promising pharmacological target in the management of chronic pain and neuroinflammation (2931, 56).…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no direct data supporting this later hypothesis, it is possible that there is differential localization of various presynaptic receptors on Vglut2+ terminals within the SNpc versus SNpr that could variably regulate the release of glutamate. It has been reported that there are various presynaptic receptors located on STN terminals, such as the cannabinoid (Sánchez‐Zavaleta et al., 2018) and GABA (Wu, Song, Faull, & Waldvogel, 2018), making it possible that these receptors are differentially distributed within various neurons of the STN.…”
Section: Discussionmentioning
confidence: 99%
“…Their activation inhibits the activity of adenylate cyclase and stimulates the protein kinase activated by mitogenesis (MAPK) as well as phosphoinositide 3-kinase (PI3K). Both receptors are distributed in the presynapses of both excitatory and inhibitory neurons, inhibiting voltage-regulated Ca 2+ channels and inhibiting the vesicular release of neurotransmitters such as γ-aminobutyric acid (GABA) and glutamate [ 17 , 18 , 25 ]. This cannabinoid-mediated response is a retrograde inhibitory signaling system that plays an important role in maintaining homeostasis in the CNS [ 26 , 27 ].…”
Section: The Endocannabinoid System (Ecs)mentioning
confidence: 99%
“…This makes sense, as the neurogenic process has been described to be a tightly regulated process [ 65 , 66 ]; for that reason, a strong stimulus may be necessary to disrupt this regulation. Additionally, it should be noted that the ECS is strongly associated with the modulation of GABAergic and glutamatergic neurotransmission [ 17 , 18 , 25 ]. Therefore, these synaptic mechanisms may participate in the neurogenic effect reported for CB1/CB2 stimulation.…”
Section: Cannabinoid Effect On Neurogenesismentioning
confidence: 99%